The Combination of Legal System: Reconciliation of Divorce Cases in Dayak Ngaju Customary Law and Positive Law Systems - Ibnu Elmi Acmad Slamat Pelu; Ahmad Dakhoir; Go Lisanawati; Jefry Tarantang (JURNAL AKTA, 2022)
This study aim to observe a legal rationale regarding a legal-system implementation of Dayak Ngaju customary dispute reconciliation in Kuala Kurun, Gunung Mas Regency, Central Kalimantan Province. In practice, the researchers found a combination performed autonomously in the legal system. Such combination was a society’s belief in using both customary legal system and positive legal system. The idea of this combination was underlined by a reflection of legal rationale finding two legal systems (customary and positive) functioned respectively where suitability occurred between legal culture of living law and formal law. The principle of a combination of legal system was an evidence of a new insight or a new paradigm through factual and norm elaborations from Dayak Ngaju customary divorce reconciliation case. This study used descriptive and analytical qualitative research method on the phenomenon of Dayak Ngaju customary dispute reconciliation in Central Kalimantan. The result obtained was implementation of a legal combination (both customary and national), instead of only an effort of a harmonization. However, the result show that implementation was not practically able to replace a naturalist paradigm, yet both were believed by the society to be able to achieve philosophical goal of a law, a peace.